(untitled) (Voice of History, 2023)
Muslims of Miya Patan of Pokhara practice their religion in accordance with Islamic law. The Muslims differ to the Hindus or other indigenous people in terms of religious beliefs and its practice. Hindus usually view them as the opposite religion. Because of the cultural assimilation and modernization of the society perception has been gradually changing among Muslims. Muslims of Pokhara practice their religion rigorously and liberally. Instead of young adults with modern education, religious leaders (such Maulana, Imams, and others) are reported to have very strong religious standards and values. In modern non-Muslim culture, religious belief and practice: people have forgotten the philosophical and spiritual advantages of faith. Muslims continue to follow Sariyat in all facets of their religious practice. It should be seen as a fortunate event, and we should take lesson from them. This article is based on qualitative research and aims to look at Muslim religious practice in Miya Patan of Pokhara. It makes an attempt to address the general situation of Muslim religious practices in Pokhara. In-depth interviews and library research are being used to gather data about the subjects under discussion. It is limited to historical study on the subject. Finding of the research can be generalized to study the entire situation of Muslim religious practice in Nepal.